Soluble CD30 serum concentrations in active rheumatoid arthritis under the treatment of low-dose methotrexate - Kamanli, A; Hacievliyagil, C; Godekmerdan, A; Ozgocmen, S; Ardicoglu, O (B M J Publishing Group, 2003)
[Abstract Not Available]
Annual European Congress of Rheumatology -- JUN 18, 2003 -- LISBON, PORTUGAL